A New Murine Model of Sustainable and Durable Chronic Critical Limb Ischemia Fairly Mimicking Human Pathology. Issue 2 (February 2015) - Lejay, A.; Choquet, P.; Thaveau, F.; Singh, F.; Schlagowski, A.; Charles, A.-L.; Laverny, G.; Metzger, D.; Zoll, J.; Chakfe, N.; Geny, B.
<x xml:space="preserve">Abstract</x> Objective To establish a chronic mouse model of critical limb ischemia (CLI) with in vivo and ex vivo validation, closely mimicking human pathology. Methods Swiss mice (n = 28) were submitted to sequential unilateral femoral (day 0) and iliac (day 4) ligatures. Ischemia was confirmed by clinical scores (tissue and functional damages) and methoxyisobutylisonitrile (MIBI) scintigraphies at days 0, 4, 6, 10, 20, and 30. At days 10, 20, and 30, muscle mitochondrial respiration, calcium retention capacity (CRC), and production of reactive oxygen species (ROS) were investigated, together with transcripts of mitochondrial biogenesis and antioxidant enzymes. Histological analysis was also performed. Results Clinical and functional damage confirmed CLI. MIBI scintigraphies showed hypoperfusion of the ischemic limb, which remained stable until day 30. Mitochondrial respiration was impaired in ischemic muscles compared with controls (Vmax = 7.93 ± 0.99 vs. 10.09 ± 2.87 mmol/L O2/minute/mg dry weight [dw]; p = .01), together with impaired CRC (7.4 ± 1.6 mmol/L minute/mg dw vs. 11.9 ± 0.9 mmol/L minute/mg dw; p < .001) and biogenesis (41% decrease in peroxisome proliferator-activated receptor gamma coactivator [PGC]-1α, 49% decrease in PGC-1β, and 41% decrease in nuclear respiratory factor-1). Ischemic muscles also demonstrated increased production of ROS under electron paramagnetic resonance (0.084 ± 0.029 vs. 0.051 ± 0.031 mmol/L minute/mg dw; p = .03) and with dihydroethidium staining (3622 ± 604 arbitrary units of fluorescence vs. 1224 ± 324; p < .01), decreased antioxidant enzymes (32% decrease in superoxide dismutase [SOD]1, 41% decrease in SOD2, and 49% decrease in catalase), and myopathic features (wider range in fiber size, rounded shape, centrally located nuclei, and smaller cross-sectional areas). All defects were stable over time. Conclusion Sequential femoral and iliac ligatures closely mimic human functional, clinical, scintigraphic, and skeletal muscle mitochondrial characteristics, and could prove useful for testing therapeutic approaches.